A alternância subjuntivo/indicativo, na fala de Fortaleza, em contexto de orações concessivas - Silva, Kelmy Vânia Camurça da (2023)
The investigation proposed here is part of an applied, descriptive and explanatory research, to an analysis of the spoken language of the informants/speakers from Fortaleza, with the aim of identifying the linguistic and extralinguistic factors that determine or contribute to the occurrence of the alternation subjunctive/ indicative, in a speech situation, in concessive clauses. As it is an analysis that offers a description of a variable phenomenon, in the speech community of Fortaleza, our study is anchored in Variationist Sociolinguistics, in the light of Labov (1972), and in the proposal of Neves (2000) regarding the subcategorizations of concessives they are also classified according to the modality. Furthermore, we considered some recent research that focused on the variable use of indicative and subjunctive modes (Pimpão 1999, 2012 and Carvalho 2007) and that helped us build the foundations of this research in analysis; as well as linguistic factors: tense and verbal modes of concessive clauses and the subcategorization of these clauses, as well as the verbs of embedded clauses that favor the subjunctive/indicative alternation. The extralinguistic factors evident in the analysis are presented in social variables, such as education, age group and gender of each informant. The informant was also essential for the research data. The sample selected for analysis comes from NORPOFOR database – Norma Oral do Português Popular de Fortaleza. In this sense, we will analyze the corpus prioritizing: 41 female informants and 44 male informants according to the linguistic and extralinguistic factors mentioned above. In general terms, the subjunctive was configured as predominant when encoding notions of uncertainty, doubt and hypothesis. The results also indicate that both the selection of the subjunctive and the indicative involve the action of important groups such as: tense and verb mood, the subcategorization of concessives and modality. The methodological procedures that characterize our research are: collection, coding and quantitative - qualitative data analysis using the statistical program R.